2020
DOI: 10.21474/ijar01/10663
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Genetic Analysis of Some Selected Okra Genotypes

Abstract: with an aim to study the genetic variability of selected okra genotypes. The study was laid out in Complete Randomized Block Design from March 2008 to July 2008. The studied characters were studied to find out the genetic variability, heritability and genetic advance, and correlation coefficient. The genotypes varied significantly (p< 0.01) for all of the characters studied. The phenotypic and genotypic variance was highest for plant height (252.54 and 422.78) followed by fruits per plant (6.33 and 7.19) and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…Thus, a greater potential is expected in selecting root length, root to shoot ratio shoot length and number of pods/plant among the studied progenies. Similar type of variations in genotypic and phenotypic coefficient was reported by several other researchers (Ashraf et al, 2020;Shwetha et al, 2020;Ranga et al, 2021). Using the coefficient of variation (CV%), crop plant attribute proportional degrees of variability are compared.…”
Section: Genotypic Variabilitysupporting
confidence: 66%
“…Thus, a greater potential is expected in selecting root length, root to shoot ratio shoot length and number of pods/plant among the studied progenies. Similar type of variations in genotypic and phenotypic coefficient was reported by several other researchers (Ashraf et al, 2020;Shwetha et al, 2020;Ranga et al, 2021). Using the coefficient of variation (CV%), crop plant attribute proportional degrees of variability are compared.…”
Section: Genotypic Variabilitysupporting
confidence: 66%
“…All examined traits exhibited noteworthy deviations for ANOVA which specified a wide divergence in the traits among accessions. Previous studies also recorded similar variations in VA [ [65] , [66] , [67] ], Zea mays [ [68] , [69] , [70] , [71] ], Oryza sativa [ [72] , [73] , [74] , [75] , [76] ], Cocos nucifera [ 77 , 78 ], Abelmoschus esculenthus [ 79 , 80 ], Mungbean [ 81 , 82 ] and broccoli [ 83 ] genotypes for yield, its related traits, and bioactive phytochemicals.…”
Section: Resultsmentioning
confidence: 61%
“…In our study, ANOVA has shown a noteworthy difference among traits. The literature has also shown corroborative results in agronomic traits of mungbean [63], Zea mays [64][65][66][67], Oryza sativa [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], okra [85][86][87], A. spp. [88,89], broccoli [90], and Cocos nucifera [91,92].…”
Section: Discussionmentioning
confidence: 84%